The time course of injury risk after return-to-play in professional football - Zhang, G.; Brink, M.; aus der Fünten, K.; Tröß, T.; Willeit, P.; Meyer, T.; Lemmink, K.; Hecksteden, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Injury risk in professional football remains high in the weeks following return-to-play (RTP). However, the time course of injury risk after RTP (i.e., the hazard curve) is largely unknown. Given the economic and competitive implications of injury burden, this knowledge gap impedes on RTP decision-making and post-RTP player management. Therefore, this study aimed to characterize the hazard curve for non-contact, time-loss injuries after RTP in male professional football (soccer) and to investigate the influence of the severity of index injury and the playing position. METHODS: Media-based injury records from the first German football league were collected over four seasons as previously published [1]. Time-to-event analysis [2] was employed for the non-contact, time-loss injury after RTP. The Kaplan-Meier survival function was used to calculate the cumulative hazard function, from which the continuous hazard function was retrieved by derivation. The severity of index injuries was categorized according to the time loss concept: minimal (1-3 days), mild (4-7 days), moderate (8-28 days), and severe (>28 days) [3]. The playing position was considered as the players main position when the subsequent injury occurred, including goalkeeper, defender, midfielder, and forward. RESULTS: 1623 observed and 1520 censored events from 646 players were analysed. The overall shape of the hazard curve was compatible with an exponential decline of injury risk, from an approximately two-fold level shortly after RTP towards baseline, with a half-time of about four weeks. The peak of the hazard curve was slightly delayed for moderate and more clearly for severe index injuries, as compared to minimal and mild index injuries. In contrast to other playing positions, forwards encountered a rising risk of subsequent injury after RTP. The greatest plunge of injury risk was seen in goalkeepers within the first two weeks after RTP. CONCLUSION: For the first time this study determined the trajectory of subsequent injury risk and its influencing factors in male professional football. The demonstrated approach to estimating excess injury risk after RTP is expected to support RTP decision-making in practice. Moreover, the continuous hazard curves allow for informed specification of required follow-up period in epidemiological studies and verification of the proportional hazard assumption in data analysis.